(untitled) (Mustansiria Dental Journal, 2025)
Abstract Aim: To compare the stress distributions in the cervical cavities of four different restorations using Von Mises stress under varying loading directions. Methods: Virtual restored lower first premolar models (n=4) with class V cavities were created from a sound premolar CAD model. Single restorative materials of a resin-modified GIC (model A), a conventional filler composite (CFC) (model B), a combination of short-fiber-reinforced composite-CFC (model C), and a ribbond fiber-CFC (model D) in a bilayered fasion were considered in this study. The FEA models received a 150 N occlusal load in the axial and oblique directions. The stress distribution in the enamel and dentin components of the model and restorative sections was analyzed. The maximum von Mises criterion was determined and compared between the tested models. Results: The FEA model indicated that the highest mvM was detected in the enamel structure of the premolar. Notably, greater stresses were observed in the GIC (Model A) and CFC (Model B) restorations than in the combined EverX-CFC restoration (Model C), which resulted in less stress in the enamel and dentin. Finally, the bilayered ribbond-CFC restoration (Model D) had the lowest stress values among the different components of the model. In the oblique loading scenario, all the models with various components presented higher stress values than did those with axial loading, with slightly lower stress values in the fiber-reinforced composite restorations. Conclusion: The incorporation of either glass or polyethylene fibers within the cervical composite restoration apparently enhances stress distributions on the surrounding tooth structure, thus probably improve the retention rate of the restoration.